Pengaruh Citra Merek, Inovasi Produk dan Iklan Terhadap Keunggulan Bersaing Produk Eskrim Wall’s Di Tambun Selatan, Kabupaten Bekasi - Edy Supriyantony; Aditya Jayadi (Jurnal Ekonomi dan Bisnis, 2021)
The high intensity of competition in the ice cream product industry requires businesses to have a competitive advantage that differentiates them from their competitors. Competitive advantage can be obtained through brand image building, product innovation and advertising. This study aims to determine the effect of brand image, product innovation and advertising, (partially or simultaneously) on the competitive advantage of Walls ice cream products. The research sample amounted to 160 people who were determined based on the formula "n indicators x 10" from an infinite population. The research subjects are consumers who buy Walls ice cream at Alfamart in 9 (nine) kelurahan, Tamsel Kab.Bekasi. Sampling using accidental technique, using a questionnaire as a data collection instrument that was tested  with validity and reliability testing techniques. The data analysis technique used multiple linear regression analysis, t-value test, and Anova F-value test. Based on the test results show, either partially or simultaneously, brand image, product innovation and advertising have a positive and significant impact on the competitive advantage of Walls ice cream products. Based on the coefficient of determination test, an "adjusted R-square" value of 0.515 was obtained which indicates that 51.5 percent of the competitive advantage variables can be explained by independent variables, the remaining 48.5 percent is explained by other variables outside the regression equation model of this study